The utilisation of biliary organoids for biomedical applications - Lei, Zhongwen; Yang, Yijun; Xiang, Yang (Frontiers in Bioengineering and Biotechnology, 2025)
Biliary duct injury, biliary atresia (BA), biliary tract tumors, primary sclerosing cholangitis (PSC), and other diseases are commonly encountered in clinical practice within the digestive system. To gain a better understanding of the pathogenesis and development of these diseases and explore more effective treatment methods, organoid technology has recently garnered significant attention. Organoids are three-dimensional structures derived from stem/progenitor cells that can faithfully mimic the intricate structure and physiological function of tissues or organs in vitro. They provide a valuable platform for studying the pathogenesis of biliary tract diseases and offer novel possibilities for repairing and regenerating biliary tract injuries. The main seed cells used to construct biliary tract organoids include primary human biliary tract epithelial cells as well as pluripotent stem cells. The construction of these organoids involves various techniques such as traditional embedding technology, rotary culture technology, hanging drop culture technology, along with emerging approaches like organ chip technology, three-dimensional (3D) printing technology, and four-dimensional (4D) printing technology. This article comprehensively reviews the construction methods of biliary tract organoids while discussing their applications in disease modeling research on disease mechanisms drug screening tissue/organ repair; it also highlights current challenges and suggests future research directions regarding biliary tract organoids which will serve as references for treating common refractory digestive system diseases in clinical practice.